Identification and description of mumps cases in a non-outbreak setting and evaluation of the effectiveness of mumps-containing vaccines over time. Issue 12 (1st December 2020) - Zerbo, Ousseny; Modaressi, Sharareh; Glanternik, Julia R.; Goddard, Kristin; Ross, Pat; Lewis, Ned; Klein, Nicola P.
ABSTRACT: Mumps outbreaks among previously vaccinated young adults raise concerns regarding waning vaccine immunity. This study identified, described and assessed the changing incidence of mumps cases following mumps-containing vaccination (MMR/MMRV) in a non-mumps outbreak setting. Potential cases between 1996 and 2018 were identified by the international classification of disease codes or by mumps laboratory test orders among Kaiser Permanente Northern California members. Medical charts were reviewed to confirm diagnoses, timing relative to vaccination and clinical characteristics. Among 474 potential cases, 257 (54.2%) were confirmed after chart review. A third of the cases were <10 years old at diagnosis and 48% were over 25 years. Most cases (92.2%) had parotitis and 5% of males had orchitis. Mumps rates decreased from 8.5 to 1.8/1, 000, 000 person-years as time since the second MMR/MMRV dose increased from <2 years to ≥10 years. Similarly, rates decreased from 16.3 to 3/1, 000, 000 person-years after at least 1 dose of MMR/MMRV. Mumps rates were higher among children aged ≤10 years compared with older age groups. In conclusion, in the context of a non-outbreak setting, this study suggests that waning of vaccine immunity to mumps appeared to have minimal clinical impact.